1997
DOI: 10.1093/humrep/12.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Human fertilization with round and elongated spermatids

Abstract: Human spermatids from ejaculate and testicular tissue have been utilized for evaluating human fertilization by intracytoplasmic sperm injection (ICSI) and, where possible, compared with spermatozoa utilizing sibling oocytes. Round and elongated spermatids obtained from ejaculates were either prepared through Percoll gradients or isolated and washed individually using subzonal insemination needles (SUZI; 10-14 microm internal diameter). Seminiferous tubules obtained after biopsy were placed into HEPES-buffered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 16 publications
1
26
0
6
Order By: Relevance
“…In the beginning we decided to evaluate elongated spermatid injected oocytes and observed a fertilization rate of 27.9% whereas various studies have reported 24% [48,49] and 71% [50]. Although we had piezoelectrically stimulated the oocytes of patients with elongated spermatids; our data is still similar to non-activated studies.…”
Section: Groupssupporting
confidence: 60%
“…In the beginning we decided to evaluate elongated spermatid injected oocytes and observed a fertilization rate of 27.9% whereas various studies have reported 24% [48,49] and 71% [50]. Although we had piezoelectrically stimulated the oocytes of patients with elongated spermatids; our data is still similar to non-activated studies.…”
Section: Groupssupporting
confidence: 60%
“…The nucleus of these cells contains half the number of the chromosomes, thus may be injected directly into oocytes. The fertilization rate was not different between round and elongated spermatids, although the fertilization rates for round and elongated spermatids in the ejaculate were 33 and 18% respectively, compared with 22 and 38% respectively when testicular spermatids were utilized (Fishel et al, 1997). However, multiple comparisons have shown that spermatozoa and elongated spermatids gave better implantation and birth rates than did round spermatids, while spermatozoa and elongated spermatozoa were indistinguishable in their ability to support embryonic development (Ogonuki et al, 2010).…”
Section: Selection Of Spermatidsmentioning
confidence: 87%
“…More recently, it has also been shown that normal embryo development could be obtained from a sterile mouse strain after ROSI (Sasagawa et al, 1998). In addition, in the human, babies have been delivered from round and elongated spermatids (Fishel et al, 1995(Fishel et al, , 1997Mansour et al, 1996;Tesarik and Mendoza, 1996a;Tesarik et al, 1996b;Antinori., 1997;Araki et al, 1997;Vanderwalmen et al, 1997;Barak et al, 1998, Bernabeu et al, 1998Sofikitis et al, 1998), but the efficacy of the process is not yet established. Although the underlying mechanism of this technique is not fully understood, the fact that fertilization, implantation, and birth of healthy infants can occur after the injection of spermatids into oocytes has led us to use this technique for infertile couples in those cases in which the technique represented their only chance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Intact round spermatid injection (ROSI) has resulted in the delivery of healthy infants (Tesarik and Mendoza, 1996a;Tesarik et al, 1996b;Vanderzwalmen et al, 1997;Barak et al, 1998;Bernabeu et al, 1998), as has treatment with elongated spermatid injection (ELSI) (Fishel et al, 1995(Fishel et al, , 1997Mansour et al, 1996;Antinori, 1997;Araki et al, 1997;Vanderzwalmen et al, 1997;Sofikitis et al, 1998).…”
Section: Introductionmentioning
confidence: 99%